2018
DOI: 10.1111/add.14418
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between food insecurity and substance use in a cohort of women with or at risk for HIV in the United States

Abstract: Food insecurity appears to be longitudinally associated with substance use among US women with or at risk for HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 69 publications
2
31
1
Order By: Relevance
“…Although the link between food insecurity and mental health dis orders is well documented in Canada, 5,15,[18][19][20][21] our finding that severe food insecurity was associated with unintentional injuries and sui cides highlights the urgent need for more effective interventions. Given the prevalence of deaths related to drug poisoning in our sample (results not shown), our finding on unintentional injuries may partly reflect the link between food insecurity and substance use, 49,50 which is often complicated by the coexistence of HIV infec tion and depression. [51][52][53] The higher risk of death from suicides is consistent with Canadian studies documenting links between food insecurity and suicidal ideation and attempts.…”
Section: Discussionmentioning
confidence: 80%
“…Although the link between food insecurity and mental health dis orders is well documented in Canada, 5,15,[18][19][20][21] our finding that severe food insecurity was associated with unintentional injuries and sui cides highlights the urgent need for more effective interventions. Given the prevalence of deaths related to drug poisoning in our sample (results not shown), our finding on unintentional injuries may partly reflect the link between food insecurity and substance use, 49,50 which is often complicated by the coexistence of HIV infec tion and depression. [51][52][53] The higher risk of death from suicides is consistent with Canadian studies documenting links between food insecurity and suicidal ideation and attempts.…”
Section: Discussionmentioning
confidence: 80%
“…19 Equally, food insecurity and food insufficiency are known risk factors for poor mental health, including depression and anxiety. 24,25,29 In addition to feelings such as hunger, exhaustion, worry, and frustration that may directly give rise to depressive and anxious symptoms, the experience of food insecurity in the U.S. is often characterized by salient stigma, shame, and self-blame. 47,48 Qualitative research has shown that these latter aspects of food insecurity often reflect a perceived failure of self-sufficiency and personal success among affected individuals, which is particularly damaging amid the individualist interpretations of wealth and achievement that are culturally prominent in the U.S. 47 In this respect, food insecurity is a profoundly relational experience that derives much of its potency from the context in which it occurs.…”
Section: Resultsmentioning
confidence: 99%
“…25,27 This finding has been shown in diverse geographical contexts and across a wide range of mental health outcomes. 25,[28][29][30][31] However, prior studies examining the association between food insecurity and mental health have not examined individual symptoms (in particular worrying and little interest, in addition to anxiety and depression). 32 Furthermore, there is a paucity of data on how receipt of food aid may modify the association between food insecurity and mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative studies in both PLWH and HIV-seronegative persons have identified feelings of helplessness, shame, and humiliation as central to the experience of FI. 16 Likewise, quantitative studies have confirmed an association of household FI with depression, anxiety, psychological distress, illicit substance use, 24 and worse overall mental health status. 9,13,25 Depression, poor mental health, and illicit substance use in turn predict ART nonadherence, higher viral loads, CD4 + T lymphocyte count decline, increased probability of AIDSdefining illness, and AIDS-related mortality.…”
Section: Mental Health Pathsmentioning
confidence: 95%